Protective Effects of Lysergol against Complete Freund Adjuvant-Induced Rheumatoid Arthritis in Rats - Wang, Lian; Ma, Li Yan; Yue, Yu Ting; Xu, Ling Ling; Lai, Jian Ming (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Rheumatoid Arthritis (RA) is a rapidly developing autoimmune disease caused by self-destruction of the immune system, resulting in deformed joints and erosion of the bones. In the current study, we explored the anti-arthritic impact of Lysergol against the Complete Freund Adjuvant (CFA)-stimulated arthritis in rat model. Materials and Methods Administration of CFA was performed for inducing arthritis and the animals were divided into 4 distinct groups. The rats then received Lysergol at a dose of 20 mg/kg. The body weight, paw swelling, arthritic index score, inflammatory cytokine levels and other inflammatory parameters were assessed along with the histopathological examination. CFA-stimulated arthritic animals treated with Lysergol substantially increased the body weight and reduced the paw swelling, organ index and arthritic index. Results Lysergol-treated rats further suppressed the levels of inflammatory cytokines including TNF-α, IL-6, IL-10 and IL-1β. Lysergol treatment also decreased the levels of Prostaglandin E2 (PGE2), Nitric oxide and Thromboxane B2 (TXB2), as well as C-Reactive Protein (CRP) and Cyclic Citrullinated Peptide (CCP). Conclusion The present investigation thus found that Lysergol may be an appropriate substitute to the currently available treatments for RA, since it exhibits a remarkable anti-inflammatory effect against CFA-stimulated arthritis in rodent models.
Keywords: Arthritis; Lysergol; Complete Freund adjuvant; Anti-inflammatory; Inflammatory cytokines